2012
DOI: 10.1111/j.1475-4983.2012.01132.x
|View full text |Cite
|
Sign up to set email alerts
|

Scutelluid trilobites from the Silurian of New South Wales

Abstract: Twenty-six species

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(56 citation statements)
references
References 35 publications
(50 reference statements)
3
53
0
Order By: Relevance
“…cylindrical at best), may invite the systematic position of Paralejurus within the Scutelluidae to be reconsidered. At first sight, illaenimorph traits such as a high convexity of the exoskeleton, a broad axis and a rather high degree of effacement of furrows together with the capacity of complex volvation might indicate close phyletic relationships with effaced late styginids of the Rhaxeros group (Lane and Thomas 1980;Holloway and Lane 1998) and especially Liolalax Holloway and Lane 1999 (see discussion in Schraut and Feist 2004). However, as pointed out by Whittington (1999) and Schraut and Feist (2004), the scutelluids differ from the styginids in having a different pattern of glabellar impressions, articulating half-rings with terrace ridges, hinges on the adaxial pleurae, and 7 paired pleural ribs besides a single, often bifurcated, median one in the pygidium, all features displayed by Paralejurus.…”
Section: Systematic Position Of Paralejurusmentioning
confidence: 98%
“…cylindrical at best), may invite the systematic position of Paralejurus within the Scutelluidae to be reconsidered. At first sight, illaenimorph traits such as a high convexity of the exoskeleton, a broad axis and a rather high degree of effacement of furrows together with the capacity of complex volvation might indicate close phyletic relationships with effaced late styginids of the Rhaxeros group (Lane and Thomas 1980;Holloway and Lane 1998) and especially Liolalax Holloway and Lane 1999 (see discussion in Schraut and Feist 2004). However, as pointed out by Whittington (1999) and Schraut and Feist (2004), the scutelluids differ from the styginids in having a different pattern of glabellar impressions, articulating half-rings with terrace ridges, hinges on the adaxial pleurae, and 7 paired pleural ribs besides a single, often bifurcated, median one in the pygidium, all features displayed by Paralejurus.…”
Section: Systematic Position Of Paralejurusmentioning
confidence: 98%
“…Kobayashi & Hamada 1974;Ehiro & Kanisawa 1999;Holloway & Lane 2012;Tanaka et al 2012Tanaka et al , 2013Cocks & Torsvik 2013). To some extent the level of species endemicity may simply reflect the current understanding of, for example, trilobite and brachiopod taxonomy, and much of the fauna clearly requires revision (see, for example, revisions to the trilobite taxonomy presented by Holloway & Lane 1998. The palaeogeographical relationships of the Japanese terranes that preserve Ordovician, Silurian and Devonian sedimentary deposits remains problematic (Metcalfe 2006), not least because of the apparently mixed palaeontological signals.…”
Section: Introductionmentioning
confidence: 93%
“…Metcalfe (2006; see also Aitchison et al 1991) considered the Early and Middle Palaeozoic faunas and floras of the Kurosegawa Terrane to have affinities with Australia and suggested a north Australian Gondwanan margin origin for this terrane. Analysis of trilobites from the Silurian of New South Wales has identified probable conspecific species of the widespread trilobite genus Japonoscutellum (J. magnum and J. diascetum) with the Kurosegawa Terrane, and Bumastella spicula is a confirmed link between the two regions (Holloway & Lane 1998. In contrast, Kido and Sugiyama (2011) showed that all of the rugose coral genera present in the Gionyama Formation also occur in the Ningqiang Formation of South China, but they also demonstrate a number of genera in common with the Silurian of Tarim, North China and Australia.…”
Section: Summary Of the Kurosegawa Terranementioning
confidence: 99%
“…In this paper we focus on six groups of Japanese trilobites that have recently undergone taxonomic revision, and which are interpreted to have a range of paleoecologies. Recent revision of the Illaenidae and Scutelluidae (Holloway & Lane, , , ) has demonstrated links between the trilobite faunas of Japan and Australia. It should be noted that the composition and delimitation of the families Illaenidae and Scutelluidae remain contentious, particularly so far as their effaced (illaenimorph) taxa are concerned (Holloway & Lane, , , ; Lane & Thomas, ; Whittington, ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent revision of the Illaenidae and Scutelluidae (Holloway & Lane, , , ) has demonstrated links between the trilobite faunas of Japan and Australia. It should be noted that the composition and delimitation of the families Illaenidae and Scutelluidae remain contentious, particularly so far as their effaced (illaenimorph) taxa are concerned (Holloway & Lane, , , ; Lane & Thomas, ; Whittington, ). Of the taxa belonging to those families dealt with in this paper, Bumastella, Rhaxeros and Lalax are assigned to the Illaenidae and Japonoscutellum , Illaenoscutellum , Kosovopeltis and Borenoria to the Scutelluidae, following Holloway and Lane (, , ).…”
Section: Introductionmentioning
confidence: 99%